2013
DOI: 10.1007/s10461-013-0538-5
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary RCT of CBT-AD for Adherence and Depression Among HIV-Positive Latinos on the U.S.-Mexico Border: The Nuevo Día Study

Abstract: We conducted a preliminary RCT among 40 HIV-positive Latinos of Mexican descent on the U.S.-Mexico border who indicated imperfect adherence and depressive symptomatology. Participants were randomly assigned to culturally adapted cognitive-behavioral therapy for adherence and depression (CBT-AD) with an alarmed pillbox or usual care. Outcomes were depressive symptoms (self-report and blind clinician ratings), adherence (self-report and electronic pillbox), and biological markers. The intervention, delivered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 58 publications
6
69
0
3
Order By: Relevance
“…The beneficial effect of CBT observed in our study actually reflected the outcome of various international studies undertaken so far [28,29,[31][32][33]. But CD4 count did not show any significant difference between 2 groups after CBT sessions as opposed to the finding in some of the recent studies [32,33]. When we looked at various factors responsible for non-adherence to ART, polarized thinking (27%), mind reading (27%) and magnification (20%) were found to be the major ones and in fact, some of the patients were having more than one factor together.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The beneficial effect of CBT observed in our study actually reflected the outcome of various international studies undertaken so far [28,29,[31][32][33]. But CD4 count did not show any significant difference between 2 groups after CBT sessions as opposed to the finding in some of the recent studies [32,33]. When we looked at various factors responsible for non-adherence to ART, polarized thinking (27%), mind reading (27%) and magnification (20%) were found to be the major ones and in fact, some of the patients were having more than one factor together.…”
Section: Discussionsupporting
confidence: 83%
“…The study showed a significantly better mean adherence level and Beck's depression score in patients of the intervention group. The beneficial effect of CBT observed in our study actually reflected the outcome of various international studies undertaken so far [28,29,[31][32][33]. But CD4 count did not show any significant difference between 2 groups after CBT sessions as opposed to the finding in some of the recent studies [32,33].…”
Section: Discussionsupporting
confidence: 74%
“…The interventions reviewed ranged from individual counseling to text messaging to computerized self-administered approaches among various populations, such as youth [32, 33], newly released inmates [34], transgender women [35], and adults with low health literacy [36]. Among those interventions for adults, some had samples that were predominantly African American [32], except for two that were specifically developed for Hispanic and Latino individuals [37, 38]. Among those integrating technological components, one intervention used a self-administered computer program [39], three used text messages [4042], one was a self-administered ART adherence breathalyzer [43], and another a mobile application [44] for use with smartphones.…”
Section: Resultsmentioning
confidence: 99%
“…Although our findings may be generalisable to other strong ART programmes with high adherence levels, in some settings adherence is most likely an important mediator between depression and attrition, and adherence-related support may represent an important intervention. Results from a small randomised study conducted in Mexico raise the possibility that treatment of depression may be a requirement for a sizeable and sustained improvement in adherence for HIV-infected adults with depression 40. Further study of the biological mechanisms responsible for the relationship between depression and adverse ART outcomes will inform the management of patients with these two conditions.…”
Section: Discussionmentioning
confidence: 99%